(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Additive manufacturing is a relevant technology for tissue engineering applications. However, due to some limitations in terms of the printing heads being used it is difficult to create complex multi-material hierarchical structures resembling natural tissues. The combination of 3D printing and microfluidics has the potential to overcome these limitations allowing to engineer functional artificial tissues with complex architectures. To achieve this a novel negative protrusion compression co-axial nozzle with a small expanding chamber is proposed in this paper, allowing balanced fluid flow conditions and uniform core-shell fibers.